Pengaruh Cafe Atmosphere, Service Quality dan Perceived Value Terhadap Customer Satisfaction di Meramoe Kota Pontianak - Al Vayyed Shalatar Barqah Djus; Pebrianti, Wenny; Juniwati, Juniwati; Heriyadi, Heriyadi; Purmono, Bintoro Bagus (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of cafe atmosphere, service quality and perceived value on customer satisfaction at Kedai Kopi Meramoe. The research design used is causal research with a quantitative approach. Data were collected through a questionnaire based on a Likert scale (1–5) and distributed to 97 respondents selected through purposive sampling techniques. Data analysis was carried out using multiple linear regression with validity, reliability, classical assumptions, and hypothesis testing (t-test and F-test). The results of the study are expected to provide empirical insight into the extent to which cafe atmosphere, service quality and perceived value contribute to customer satisfaction at coffeeshop Meramoe.